2017
DOI: 10.1093/brain/awx154
|View full text |Cite
|
Sign up to set email alerts
|

Cell-based therapeutic strategies for multiple sclerosis

Abstract: Cell-based therapies, including autologous haematopoietic stem cell transplantation, have generated substantial interest as strategies for immune modulation, neuroprotection, or repair of the damaged CNS in multiple sclerosis. Scolding et al. summarise the status of cell-based therapies and make consensus recommendations for future studies and clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 145 publications
1
91
0
1
Order By: Relevance
“…This data is in agreement with other studies and recent guidelines33 and confirms the important role of AHSCT as a therapeutic option for patients with RRMS. Data from the first phase III randomised controlled trial of AHSCT in MS (the MIST trial)34 showed a significant difference in NEDA rates between transplant and conventional MS DMT arms; however, the heterogeneity of the DMT arm means planned studies of AHSCT versus high efficacy immunotherapy are awaited with interest 35.…”
Section: Discussionsupporting
confidence: 93%
“…This data is in agreement with other studies and recent guidelines33 and confirms the important role of AHSCT as a therapeutic option for patients with RRMS. Data from the first phase III randomised controlled trial of AHSCT in MS (the MIST trial)34 showed a significant difference in NEDA rates between transplant and conventional MS DMT arms; however, the heterogeneity of the DMT arm means planned studies of AHSCT versus high efficacy immunotherapy are awaited with interest 35.…”
Section: Discussionsupporting
confidence: 93%
“…It is encouraging to note that such studies are now underway. Cell-based therapies include depletion of the immune system via immunoablation, followed by mesenchymal and related stem cell transplantation, autologous hematopoietic stem cell transplantation, transplantation of oligodendrocyte progenitor cells, and introduction of endogenous stem cells followed by enhancement of their reparative capabilities [85]. Although these are potentially breakthrough treatment approaches, there are methodological and ethical challenges in designing such studies, and our understanding of potential benefits and safety concerns is limited, thereby relegating these approaches to aggressive or hard-to-treat MS for which treatments are desperately needed but few are available.…”
Section: Cell-based Immunotherapiesmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs), which have been isolated from bone marrow, umbilical cord, dental pulp, and a diversity of other tissues, have the ability of differentiating into tissue‐specific lineages . An increasing number of studies have demonstrated promising applications of MSCs in regenerative medicine and tissue engineering to repair and regenerate damaged or lost tissues due to diseases and traumatic injuries and, nonetheless, translational uses of MSCs remain inefficacious, in part due to their limited capability of migrating and homing . Thus, gaining insights into the mechanisms regulating MSC migration can provide useful information for developing novel strategies to prepare MSCs for clinical applications and improve the efficacy of MSC‐based therapies as well as evolving a better understanding of the contentious MSC biology .…”
Section: Introductionmentioning
confidence: 99%